Sekurytyzacja ryzyka pandemii - Małek, Aleksandra (Pandemics Risk Securitization, 2008)
Humanity has had to deal with the destructive force of the plaques and the ravaging diseases since prehistory. Pandemics have been a part of the insurance industry since its beginnings. However, today's pandemics risk is no longer a result of, hygienic or medical conditions. The risk exposure has to take into account traveling possibilities and new mutations of the present pathogens. For the insurance industry there is a special need to devise new solutions of risk transfer. Securitization as a financial innovation has become a substitute for classical transfer methods. This paper identifies some new aspects of pandemics risk. There is also a compact introduction to the securitization methods in the life insurance industry. Finally the paper tries to examine securitization programs and catastrophe bonds transferring pandemic risk to the capital markets.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 18, s. 68-78